The Development of an Android Studio-Based E-Module to Optimize Students' Understanding of Sauce Material in Continental Food Courses - Anugerah, Ajeng Inggit; Agustina, Dian; Akmal, Nikmat; Waruwu, Mawadda Azizah Sari (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to develop and test the effectiveness of an Android Studio-based e-module to optimize students' understanding of sauce material in the Continental Cuisine course. The e-module integrates systematic learning content with interactive features such as tutorial videos, quizzes, and simulations. The study follows the ADDIE model through analysis, design, development, implementation, and evaluation. The findings indicate that the developed e-module significantly improves students' comprehension of sauce concepts, as evidenced by higher post-test scores compared to pre-test results. Experts' validation and students' responses also confirmed the feasibility and usability of the e-module as a supporting digital learning media.